Novel prediction models of earthquake early warning for ground motion power in Taiwan - Chao, Shu‐Hsien; Lin, Che‐Min; Chou, Chung‐Che; Chen, Kuan‐Hua (Earthquake engineering & structural dynamics, 2024)
Studies have indicated that the power of seismic waves, rather than the acceleration and velocity, strongly correlates with the level of structural damage and the shutdown of high‐tech equipment during high‐precision process. However, current earthquake early warning (EEW) systems in Taiwan issue a warning only for a seismic wave with high acceleration or velocity but not for that with high power. To extend the application of the EEW system to high‐tech fields, conventional and novel hybrid prediction models were developed in this study to predict the ground motion power and to issue EEWs for high‐power ground motions. A conventional prediction model that relies on earthquake source parameters was first developed to determine ground motion characteristics, and a hybrid prediction model that relies not only on earthquake source parameters but also on the on‐site ground motion parameter of P‐waves was developed to improve the prediction accuracy. The two‐step maximum likelihood method was used to derive model coefficients for considering the mixed effect of the ground motion records. The source, path, and site effects on the short‐period power and the long‐period power of ground motions were illustrated by the proposed models. A method for determining a broadcast scenario of EEW systems for high‐power ground motions with a target success rate and damage threshold was also developed. These novel prediction models can be used to develop a customized EEW system to provide an early warning for high‐power seismic waves in Taiwan.